Difficult paths: Slow progress in preventing wrongful convictions in China. (March 2018) - Jiang, Na
Abstract: China has made new changes to its criminal justice system, as stated in the 2016 White Paper. In this sense, all reforms leading to the prevention of wrongful convictions can be regarded as an essential step towards a modern justice system. But police torture continues to occur because of a lack of judicial and prosecutorial restraints on police actions. The danger of ineffective defence against tortured confessions in the Chinese context is so grave that the underlying aim of the reforms has actually been defeated. This article assesses what effects the reforms have had on China's practice and whether or not they will prevent future wrongful convictions. The latest data and case studies will demonstrate the main pitfalls of the reforms, both in how the new laws or regulations are written and how they are implemented. Further substantive reforms are needed to achieve better justice and more human rights progress.